A cross sectional study to investigate the prevalence of metabolic syndrome in clinically diagnosed patients of psoriasis vulgaris in South Gujarat - Gundavda, Pankti Manit; Patil, Priyanka Chandrakant; Umrigar, Dipak D. (International Journal of Research in Dermatology, 2020)
Background: Psoriasis is a common, chronic, inflammatory keratinization disorder of the skin. It can be triggered by many environmental as well as genetic factors. The metabolic syndrome (syndrome X, insulin resistance syndrome) consists of a constellation of metabolic abnormalities that confer increased risk of cardiovascular disease (CVD) and diabetes mellitus (DM). Often coexistence is noticed between psoriasis and metabolic syndrome. Methods: A cross-sectional study was conducted in the Government medical college and new civil hospital, Surat. A total of 115 clinically diagnosed cases of psoriasis vulgaris and similar age and sex matched controls visiting dermatology out patients’ department of new civil hospital, Surat were selected for the study. Results: Prevalence of metabolic syndrome is significantly higher in psoriatic patients after the age of 40 years, and it directly correlates to psoriasis duration. No association observed with gender, percentage of body surface area involved and smoking, but in patients of 18-40 years with metabolic syndrome had significantly higher percentage of body surface area involved as compared to >40 years age group. Patients with metabolic syndrome had mean disease duration of 5.52±5.83 years and BMI was 27.48±4.36. Conclusions: Higher prevalence of metabolic syndrome in patients with psoriasis could play a relevant role in accelerating atherosclerosis. All patients with psoriasis should be encouraged to aggressively correct their modifiable cardiovascular risk factors.